The caries prevalence, def–t index and DMF–T index of deaf children at the primary school of special education Kota Kinabalu in Sabah - Melissa May Joe; Eka Chemiawan; Jakobus Runkat (Faculty of Dentistry Universitas Padjadjaran, 2007)
Deaf is the loss of hearing partially or even totally and could happen congenitally or acquired. The purpose of this research was to find out the information on the caries prevalence, def-t and DMF-T index of Deaf children at the Primary School of Special Education in Kota Kinabalu, Sabah year 2008. This study was a descriptive research with survey technique. All samples, 43 primary students of Primary School of Special Education in Kota Kinabalu, Sabah from kindergarten to primary six. The def-t and DMF-T index standard used the WHO criteria, namely, very low (0.1-1), low (1.2-2.6), moderate (2.7-4.4), high (4.5-6.5), and very high (>6.5). The results of this research indicate that the caries prevalence of the Deaf children year 2008 was 95.3%. the def-t index was 2.81 and DMF-T index was 1.67. The conclusion of this research was that the average def-t index included in moderate criteria and the DMF-T index was low.